Morphological and Molecular Observation to Confirm the Taxonomic of Coptocercus biguttatus (Coleoptera: Cerambycidae) on Cloves in Ambon and Part of Ceram Island - Mohamad Pamuji Setyolaksono; Suputa Suputa; Nugroho Susetya Putra (Jurnal Perlindungan Tanaman Indonesia, 2017)
This research was conducted to confirm the species of longhorn beetle (Coptocercus biguttatus) drilling clove stems in Ambon and part of Ceram Island, Moluccas, which has been noted as an important pest. Aim of this investigation was to characterize the species morphologically, and more detailed with molecular technique via mtCO1 gene analysis. The longhorn beetle was taken in Ambon and part of Ceram Island, Moluccas and then was etablished in laboratory with host rearing method on pieces of clove stem. The results showed that C. biguttatus attacking clove stems in Ambon and part of Ceram Island, Maluku was closely related and grouped into same cluster with C. rubripes and P. semipunctata in of New Zealand with 85% homology value. C. biguttatus distributed evenly in all clove planting areas in Ambon and part of Ceram Island. IntisariPenelitian ini dilakukan untuk mengonfirmasi spesies kumbang sungut panjang (Coptocercus biguttatus) yang menggerek batang tanaman cengkih di Pulau Ambon dan sebagian dari Pulau Seram, Maluku menggunakan karakter morfologi dan molekuler berbasis gen mtCO1 untuk sidik kekerabatan. Pengambilan sampel kumbang sungut panjang dilakukan di Pulau Ambon dan sebagian dari Pulau Seram, Maluku dengan cara host rearing pada potongan batang cengkih. Hasil penelitian menunjukkan bahwa C. biguttatus di Pulau Ambon dan sebagian dari Pulau Seram, Maluku berkerabat dekat dan berada dalam satu kelompok dengan C. rubripes dan P. semipunctata di New Zealand dengan nilai homologi 85%. Penyebaran C. biguttatus di Pulau Ambon dan sebagian dari Pulau Seram merata di seluruh area pertanaman cengkih.